Depression, anxiety and stress study amidst COVID-19 in dental undergraduates - Madhikarmi, Nirjala Laxmi; Shrestha, Aastha; Pandey, Santwana (Journal of Physiological Society of Nepal, 2021)
Introduction: Persistent stress can impair the student’s wellbeing leading to diminished efficiency at work or learning. Dental students are frequently exposed to various stressors that are related to treatment procedures, training and administrative challenges in the college. The aim of the present study is to assess the stress, anxiety and depression levels of dental students during COVID-19. This study aimed to examine the impact of depression, anxiety and stress during COVID-19 pandemic. Materials and methods: This cross-sectional study was conducted in Kantipur Dental College Teaching Hospital & Research Center, Kathmandu Nepal during covid-19 pandemic. The study was conducted with 150 students with 50 students each from first year, second year and third year. Levels of depression, anxiety, and stress were measured using the Depression, anxiety and stress scale -21 (DASS-21); statistical analysis were performed using SPSS 20.0 and p<0.05 was considered level of significance. Results: The total DASS score was calculated as 33.76 ± 23.12, the students showed normal, mild, moderate, severe and extremely severe groups but the maximum frequency was in normal DASS group. The study included four times more female students than male, only 27.33% did regular exercise, 40% reported financial burden on dental study. Conclusions: A significant relation both on academic as well as social life factors of DASS was noticed on dental undergraduates during COVID-19 which is an alarming situation, emphasizing need of intervention, with the development of appropriate support services for this group.